APPLICATION OF CARBON FIBER V-BELTS IN LATHE MACHINES TO IMPROVE DURABILITY - Primintiyan Sukma Aji Wibowo; Marsono Marsono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to analyze the durability of using carbon fiber v-belts on lathe machines. Development of a v-belt designed using carbon fiber as an additional material. The V-belt is a component that drives a lathe by rotating the fan on the machine. This is because the addition of carbon fiber as a v-belt material can increase the longevity of the v-belt. The research used a hypothesis method to determine the comparison of v-belt life durability, where H0 stated that the addition of carbon fiber to the v-belt had a significant effect on the v-belt life expectancy on the lathe. Meanwhile, H1 states that the addition of carbon fiber to the v-belt has no real effect on the longevity of the v-belt on the lathe.